Global expert consensus on Takotsubo syndrome (part I): understanding clinical presentation, diagnostic criteria, and underlying mechanisms - Khan, M. Toufique; Yeasmin, Mahbuba; Sraya, Tasmiah Islam; Akther, M. Sharmin; Pramanik, Solaiman (International Journal of Research in Medical Sciences, 2025)
Takotsubo syndrome (TTS), also known as stress-induced cardiomyopathy or broken heart syndrome, is an acute, reversible form of left ventricular dysfunction that clinically mimics acute myocardial infarction but occurs without significant coronary artery obstruction. First identified in Japan in the 1990s, TTS is now recognized globally and accounts for approximately 1-2% of patients with suspected acute coronary syndrome. It predominantly affects postmenopausal women (mean age 58-75 years) and is typically triggered by intense emotional or physical stress. Clinically, TTS presents with sudden chest pain, dyspnea, and ECG changes such as ST-segment elevation or T-wave inversion. The leading pathophysiological hypothesis involves a catecholamine surge leading to myocardial stunning, microvascular dysfunction, and direct myocardial toxicity. Additional factors include neurohormonal, endothelial, and metabolic disturbances. Diagnosis is largely clinical, based on exclusion of coronary artery disease and confirmed via imaging modalities like echocardiography or cardiac MRI, which show characteristic regional wall motion abnormalities, often termed "apical ballooning." The Mayo Clinic Criteria remain the most widely accepted diagnostic framework, emphasizing transient ventricular dysfunction, absence of obstructive coronary lesions, ECG/biomarker abnormalities, and eventual recovery. Although the short-term prognosis is generally favorable, complications such as heart failure, arrhythmias, and thromboembolism may occur. Recurrence rates range from 5-15%, and psychological distress may persist. This review outlines the clinical presentation, diagnostic approach, and pathophysiological insights into TTS, highlighting recent consensus and advances essential for accurate diagnosis and long-term care.